2018
DOI: 10.1111/jgh.14286
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term course of inflammatory bowel disease after the Great East Japan Earthquake

Abstract: The relapse rates 1 and 2 years after the earthquake significantly decreased. The factors that influenced long-term relapse were different from those that influenced short-term relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…Conversely, in medium-long term (up to 5 years), a significant difference on the slope decrease of hospitalizations for acute and chronic respiratory diseases in the earthquake vs. the neighbor geographical areas. Consistently, also studies investigating the incidence rates of IBD flare-ups after the Great East Japan Earthquake showed an increase in the short follow-up period (after 4 months) and a normalization within the expected rates in the long run (after 24 months) (21,22).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Conversely, in medium-long term (up to 5 years), a significant difference on the slope decrease of hospitalizations for acute and chronic respiratory diseases in the earthquake vs. the neighbor geographical areas. Consistently, also studies investigating the incidence rates of IBD flare-ups after the Great East Japan Earthquake showed an increase in the short follow-up period (after 4 months) and a normalization within the expected rates in the long run (after 24 months) (21,22).…”
Section: Discussionsupporting
confidence: 66%
“…Life-event stress induced by the earthquake was associated with higher relapse rates in UC but not CD patients mediated by changes in diet and family finances worries (21). In contrast, relapse rates decreased significantly at the 2-years follow-up, even though time-to-event analyses showed a significant 2-fold increase of needed additional medical treatment in patients who had experienced the death of family members or friends (22).…”
Section: Introductionmentioning
confidence: 92%
“…One observational study after a devastating earthquake reported that patients with IBD who had experienced the death of family members or friends were likely to need additional treatments. 28 This study indicated that depression could be a cause of worsening disease activity rather than depression being a result of a poor clinical course. Furthermore, this result indicates that the disease activity of patients with UC who have depressive symptoms could be improved by prompt intervention performed by a psychiatrist, which might ultimately contribute to an improved prognosis.…”
Section: Discussionmentioning
confidence: 82%
“…We have been conducting a prospective questionnaire survey to investigate the causal relationship. One observational study after a devastating earthquake reported that patients with IBD who had experienced the death of family members or friends were likely to need additional treatments 28 . This study indicated that depression could be a cause of worsening disease activity rather than depression being a result of a poor clinical course.…”
Section: Discussionmentioning
confidence: 95%
“…Acute and chronic stress may affect IBD disease activity [7,11,12]. For example, a study showed an increase frequency of disease relapse in IBD patients following the Great East Japan earthquake of March 2011 [13]. However, it is not known how the stress during a pandemic impacts the disease activity.…”
Section: Introductionmentioning
confidence: 99%